ANALISIS PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN (Studi pada nasabah PT. Prudential Life Assurance Semarang) - Raharja, Aryawan Tri; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
Based on the increasing number of customer complains received by the company, this research was conducted to determine how service quality (X1), product quality (X2) and customer value (X3) affects customer satisfaction (Y) in PT. Prudential Life Assurance Semarang, and to analyze which of them are the one with greatest influence on PT. Prudential Life Assurance Semarang’s customer satisfaction. Population of the study are holders of PT. Prudential Life Assurance’s insurance policy in the Semarang area. Sample of the study consisting of 100 people as respondents, taken using non probability sampling technique. Data types used in the research are both primary and secondary data acquired from questionnaires and literature studies. Techniques of analysis used in the research consisting of validity, reliability, classical assumption tests, and multiple regression. Also included in the research are statistical hypothesis tests and coefficient of determination test. Multiple regression analysis made shows, Y = 0,306 X1 + 0,307 X2 + 0,306 X3.  The test proven product quality variable as the one with greatest influence (0,307), followed service quality (0,306), and customer value (0,306). Statistical hypothesis analysis proven all independent variables has positive and significant influence on PT. Prudential Life Assurance’s insurance policy holders customer satisfaction. Coefficient determination test (adjusted R2) shows 0,598. Which indicates 59,8% of the customer satisfaction in the research are influenced by service quality, product quality, and customer value. And the rest 40,2% are influenced by other variables.